Uso do solo e conversão vegetacional: a perda da biodiversidade em dois fragmentos de cerrado Stricto Sensu no município de Goiandira (GO) - (:unkn) unknown (Universidade Federal de Goiás, 2017)
The Cerrado Biome is characterized by its heterogeneous landscape, in which it enables significant natural and social mechanisms that contribute to the maintenance of important ecological processes. However, it is not understood as Natural Patrimony, nor even evidenced by the biodiversity that constitutes it. As a consequence, it became territory for the agricultural cradle that was fomented by public policies of the Federal Government, from the decade of 1930. Since then the unsustainable exploration has been expanding, implying diverse environmental impacts. The diagnosis made during this research reiterates that the main socioeconomic activities developed in the city of Goiandira (GO) fit exactly in the above mentioned perspectives. The construction of its economic bases is closely related to the conversion of native vegetation by cultivars. In addition, it was observed in the study of land use and occupation of the municipality that the cultivated pasture classes, planting of crops and areas with central pivots, together added up to 38.04%, while the native vegetation Is conserved basically in the areas of permanent preservation, with low occurrence in soil areas suitable for cultivation. This information subsided and guided the field research composed by the floristic and phytosociological survey of two areas of Cerrado Stricto Sensu, in which, together with the floristic richness of 1,366 individuals, distributed in 48 species and 25 botanical families in 2ha. The Shannon index (H ') found for this research (3.15) was lower than the average presented in other studies in Cerrado Stricto Sensu areas of Central Brazil. The low similarity between the study areas (0.39%) point to the divergences both from the point of view of species composition and the patterns of abundance of their populations resulting from anthropic management in area B. Thus, It is believed that agricultural activities exert one of the greatest environmental pressures due to the inadequate use of natural resources that promote intense environmental degradation through the destruction of habitat and potentially useful species. In view of all this context of extinction of genetic diversity, caused by anthropic activities that drive the decline of biodiversity and the failure of natural potential, it becomes necessary to understand the structure and functioning of plant communities, as well as to subsidize, elaborate and execute Mechanisms that enable and reconcile landscape conservation with economic development.
Soil use and vegetation conversion: the loss of biodiversity in two fragments of cerrado Stricto Sensu in the city of Goiandira (GO)
Keywords: Biodiversidade; Uso do solo; Conversão vegetacional; Goiandira (GO); Biodiversity; Use of the soil; Vegetative conversion; CIENCIAS HUMANAS::GEOGRAFIA